Pentingnya Diversity Analysis Pada Perusahaan - Intania Syafrina; Nina Pramita; Dessy Astuty; Cristina Tan; Alden Nelson (STIE AMKOP, 2023)
This research was written with the aim of wanting to find out whether a company needs something called Diversity Analysis where it is known that every company has a lot of diversity then gathers in one place and is united in order to achieve company goals simultaneously. This study uses the literature research method which builds on previous research and reads sources that are still reliable Kata Kunci : Diversity; company;